2016
DOI: 10.1615/interfacphenomheattransfer.2017020203
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Moist Air Flow Near Contact Line Using Microdroplets as Tracers

Abstract: We study the trajectories of levitating microscale droplets of water in the vicinity of a contact line which is the boundary of a dry patch in a liquid layer on a heated horizontal substrate. Droplets initially form by condensation and move under the action of gravity, buoyancy, and Stokes drag force which depends on the moist air velocity. The time-dependent data on the droplet trajectories are used to obtain detailed information on the steady air velocity distributions near the contact line. An increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Таким образом, сила сопротивления приближенно записывается нами в виде [27] внимание было уделено сближению аналитических траекторий капель с экспериментальными с помощью метода наименьших квадратов. Идея использовать траектории капель для расчета скорости газа над сухой нагретой поверхностью была упомянута ранее в [40], а возможный механизм левитации капель при таких условиях обсуждался в [41]. В настоящей работе мы определяем параметр U с целью обеспечения расчетного сближения экспериментальных и аналитических сил (3) и (6), а не траекторий капель.…”
Section: аналитические приближенияunclassified
“…Таким образом, сила сопротивления приближенно записывается нами в виде [27] внимание было уделено сближению аналитических траекторий капель с экспериментальными с помощью метода наименьших квадратов. Идея использовать траектории капель для расчета скорости газа над сухой нагретой поверхностью была упомянута ранее в [40], а возможный механизм левитации капель при таких условиях обсуждался в [41]. В настоящей работе мы определяем параметр U с целью обеспечения расчетного сближения экспериментальных и аналитических сил (3) и (6), а не траекторий капель.…”
Section: аналитические приближенияunclassified
“…Professor Kabov started Kabov et al (2016) a remarkably successful series of international meetings on two-phase flows for ground and space applications, supported by the ESA. Now in its 12th year, the conference became an important event that has brought together leaders in space research and representatives of funding agencies from Europe, Russia, China, Japan, and the United States; many future space experiments were conceived and discussed at these meetings.…”
Section: Figmentioning
confidence: 99%
“…Decades later, after conducting several experimental studies of this phenomenon [9], it was found that due to intensive local heating the levitating microdroplets may organize themselves into regular structures, the so called "droplet clusters" [9,10]. In [11,12] the authors conducted a detailed analysis of trajectories of levitating microdroplets above a heated liquid layer with a dry patch. The obtained results allowed determination of local velocities of moist air in a vicinity of the contact line at the dry patch.…”
Section: Introductionmentioning
confidence: 99%
“…To describe the levitation of larger droplets above the liquid film, a vapor flow from the liquid surface was added to the model [16]. In the current paper, we built new experimental setup to conduct the experiment under more controlled conditions as compared to previous works [11][12][13]: communicating vessels were used to maintain the required liquid level on the substrate, T=const, also we made a groove on the surface of the substrate in order to keep a dry spot, since the purpose of the work was to study the evaporation of microdroplets levitating directly over a dry heated surface. In the experiment we used optics with a high spatial resolution (400 nm/pixel), 2 times higher than that used previously for the similar experiments.…”
Section: Introductionmentioning
confidence: 99%